موقف يعقوب صنوع من الحركات الإسلامية الإصلاحية في الربع الأخير من القرن التاسع عشر: المهدية نموذجا - محمد، أميرة السعيد الطنطاوي (جامعة الإسكندرية - كلية الأداب, 2018)
يعد يعقوب صنوع (١٨٣٩-١٩١٢) من أبرز المفكرين المصريين الذين كانت لكتاباتهم أثر بالغ في إحداث نهضة فكرية ليس فقط في المجتمع المصري بل في المجتمع الإسلامي أيضا، فرغم أن صنوع كان يهوديا إلا أنه اهتم بواقع المسلمين اهتماما جعل بعض الكتاب يزعمون انتسابه إلى الإسلام، أظهر اهتماما بالكتابة الصحفية فأصدر جريدة "أبو نظارة" التي كتب مقالاتها في أحيان كثيرة باللغة العامية الدارجة، وكانت الجريدة مصورة تصويرا هزليا رائعا، عبر عن آراء صنوع وأفكاره شكلت عباراته ورسومه كلا واحدا ساعد على إيضاح أفكاره ونقلها إلى قرائه، وتعددت الموضوعات التي تطرق لها صنوع في جريدته التي ظلت تصدر لمدة أربعة وثلاثين عاما، وكانت الحركة المهدية وتطورات الوضع في السودان من أهم موضوعاتها، حيث شهد القرن التاسع عشر ظهور عدد من الحركات الإسلامية الإصلاحية ذات الطابع الاستقلالي، وكانت الحركة المهدية التي ظهرت خلال الربع الأخير من ذلك القرن بزعامة محمد أحمد (١٨٤١-١٨٨٥) الملقب بالمهدي واحدة من أهم هذه الحركات التي أثرت بشكل كبير في المجتمع الإسلامي، كما كان لها تداعياتها القوية في الموقف الدولي. تتناول هذه الورقة البحثية بالدراسة موقف يعقوب صنوع من الحركة المهدية من خلال ثلاثة محاور رئيسة، يسبقها تمهيد عرفت فيه بصورة موجزة بشخصية يعقوب صنوع ودراسته واهتماماته الثقافية، ثم أوضحت في المحور الأول بداية ظهور الحركة المهدية، وعدم اكتراث يعقوب صنوع بشأنها إلا بعد الاحتلال البريطاني لمصر عام ١٨٨٢م واتخاذ بريطانيا بعض الإجراءات التي عبرت عن نيتها في التدخل للقضاء على هذه الحركة، مما دفع صنوع إلى الاهتمام بشأنها، ثم أشرت في المحور الثاني إلى موقف يعقوب صنوع من الانتصارات المهدية في فترة حكم المهدي (١٨٨٣- ١٨٨٥) وكيف أضفى صنوع هالة من التعظيم على انتصارات أتباعه، مظهرا بالغ سعادته لهزائم الإنجليز المتتالية، ومصرع كبار قادتهم على يد القوات المهدية، ثم جاء المحور الثالث ليوضح موقف يعقوب صنوع من الصراع المهدي- الإنجليزي في الفترة من (١٨٨٥-١٨٩٩) حيث حكم عبه الله التعايشي (1846-١٨٩٩) كخليفة للمهدي، فانقلبت الانتصارات المهدية في عهده إلى هزائم متتالية غض صنوع الطرف عن ذكرها، كما أنه حول في بعض الأحيان انتصارات الإنجليز إلى هزائم. أما عن مصادر البحث فقد اعتمدت بصورة أساسية على صحف يعقوب صنوع التي شكلت المصدر الأساسي لمادة البحث، هذا إلى جانب الاعتماد على بعض الصحف الإنجليزية المحاصرة للأحداث مثل لندن جازيت London Gazette، وإيفيننج بوست Evening Post حيث أوردت بعض المعلومات بشأن القوات الإنجليزية المحاربة في السودان، فساعد ذلك على المقارنة بين ما ذكره صنوع وما ذكرته تلك الصحف بشأن أحداث الحركة المهدية، بالإضافة بعض وثائق دار الوثائق القومية بالقاهرة، ولاسيما وثائق مجلس الوزراء، وعدد من الدوريات والمراجع العربية والأجنبية.
Ya'qūb Sanu (1839-1912) was one of the most prominent Egyptian intellectuals, whose writings had a profound effect on creating a renaissance of thought, not only in Egyptian society, but in Islamic society, too. Although Sanu was a Jewish, he cared a lot about the reality of Muslims, that make some writers claimed his affiliation to Islam. Sanu gave an obvious interesting the Art of theater and he was the first founder of a theater in Egypt, then he showed an interest in press writings and released "Abu-Naddara" newspaper, which often wrote its articles in a colloquial language. The newspaper had wonderful comic illustrations, which expressed Sanu's opinions and ideas. His phrases and paintings formed one unit and helped to clear his ideas and transferred them to his readers .Numerous topics that he touched in his newspaper, had been issued for thirty four years. The Mahdist movement and the situation developments in Sudan were one of her most important topics, as the nineteenth century saw the emergence number of reformist Islamic movements with independence nature. The Mahdist movement which appeared in the last quarter of that century under the leadership of Muhammad Ahmed (1843-1885) who titled with El-Mahdi was one of the most important movements, which influenced significantly in Islamic society and had strong repercussions in the international situation. This research paper deals with the studying of Ya'qūb Sanu's position from The Mahdist movement in three main axis Preceded by preliminary to characterize Ya'qūb Sanu briefly, his studying and cultural interests, In the first theme I explained the onset emergence of The Mahdist movement and Ya'qūb 's lack attention of it, until after the British occupation of Egypt in 1882 when Britain took some proceedings to express her intention to intervene and eliminate this movement, that prompted Sanu to care about it .In the second theme , I referred to Ya'qūb's position from The Mahdist victories under the rule period of El-Mahdi(1883-1885) and how imparted an aura of veneration on his followers victories appeared his happiness with the defeating British successive and the death of their senior leaders by The Mahdist troops. In the third theme, I explained Ya'qūb's position from The Mahdist -English conflict in (1885-1899) when Abdullah El Taaishy (1846-1899) ruled as a successor to El-Mahdi and The Mahdist victories changed into successive defeats. Sanu didn’t mention them, but also he sometimes changed the English victories into defeats. The research sources relied mainly on Sanu’s newspapers This formed the basic source of the research subject, beside depending on some contemporary English newspapers for events like London Gazette and Evening Post which had some information about fighting forces in Sudan and helped to compare Sanu's sayings against those newspapers about The Mahdist movement events, in addition to some documents of the Egyptian national archive in Cairo, especially Documents of the Council of Ministers, also a number of English and Arabic periodicals and references.
Keywords: صنوع، يعقوب -- الحركات الإسلامية -- الثورة المهدية -- السودان